The Effect of Teamwork and Job Satisfaction on Service Quality at Abdoel Wahab Sjahranie Hospital - dwi ida puspitasari; Muksin Muksin; Muhammad Henry Gunawan (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2021)
The purpose of this study was to determine the effect of teamwork and job satisfaction on the quality of nursing services at Abdul Wahab Sjahranie Hospital Samarinda. This study used a quantitative approach and a sample of 55 nurses were selected by simple random sampling. Data collection techniques used in this study are Service Quality, Teamwork and Job Satisfaction Scale. The three scales were prepared using a Likert scale and using SPSS (Statistical Package for Social Sciences) for the statistical analysis window. The results of this study indicate that there is a significant influence between teamwork and job satisfaction quality of nursing services, namely f count f table (15.832 3.16) and p = 0.000 (p 0.05). The contribution of teamwork and job satisfaction to service quality is 0.365 (36.5 percent). Teamwork has a significant effect on the quality of nursing services with a beta coefficient () = 0.076 and t count t table (2.715 2.005) and p = 0.028 (p 0.05). Job satisfaction has a significant effect on service quality with a beta coefficient () = 0.181 and t-count t-table (2.936 2.005) and p = 0.005 (p 0.05).